The Interaction of Formates with Water Cluster Ions - Diedhiou, Malick (Université d'Ottawa | University of Ottawa, 2024)
Over the past several decades, the study of gas-phase chemistry has emerged as a prominent area of research, particularly focusing on understanding the behavior of various molecules in the atmosphere. This research explores the gas-phase interaction of formates with water cluster ions and the resulting unimolecular dissociation of protonated and hydrated formates and chloroformates. Chapter 3 of this thesis investigates the ion-molecule reactions involving neutral methyl formate (MF) and proton-bound solvent clusters W₂H⁺, W₃H⁺, M₂H⁺, E₂H⁺, and E₃H⁺. Through experimental investigation, it was found that the primary reaction pathway involves the loss of solvent molecules from the initial encounter complex, leading to the formation of protonated methyl formate (MFH⁺). Detailed collision-induced dissociation breakdown curves were obtained for the initial solvent-MF proton-bound pairs and trimers, revealing relative activation energies for the observed channels. Density functional theory calculations (B3LYP/6-311+G(d,p)) supported barrierless reactions for solvent loss in each case. Additionally, for MF(M)H⁺ ions, the loss of CH₄ at higher collision energies was observed. The mechanism of this reaction involves the migration of the MF methyl group to form a loosely bound complex between neutral CH₄ and an ion comprised of (CH₃OH)(CO₂)H⁺. Overall, these findings demonstrate the formation of stable encounter complexes between methyl formate and atmospheric water, which subsequently dissociate to produce protonated methyl formate. In chapter 4, the focus is on ion-molecule reactions involving neutral ethyl (EF), isopropyl (IF), t-butyl (TF), and phenyl formate (PF) interacting with proton-bound water clusters W₂H⁺ and W₃H⁺ (where W=H₂O). It was observed that the primary reaction product entails the loss of water from the initial encounter complex, subsequently leading to the formation of protonated formate. Utilizing collision-induced dissociation, breakdown curves of the formate-water complexes were generated, allowing for the extraction of relative activation energies for the identified channels. Density functional theory calculations, employing the B3LYP/6-311+G(d,p) method, further supported these findings by revealing that the water loss reactions exhibit no reverse energy barrier in each instance. Overall, the outcomes suggest that the interaction between formates and atmospheric water can yield stable encounter complexes that eventually dissociate, resulting in the formation of protonated formates. Chapter 5 further expands on the atmospheric fate of formate-derived esters through the exploration of their dissociation pathways upon protonation. Tandem mass spectrometry serves as the primary tool for studying the unimolecular dissociation of protonated methyl-, ethyl-, isopropyl-, tert-butyl-, and phenyl formate. Key findings reveal distinct fragmentation patterns: methyl- and ethyl formate ions lose CO to form protonated alcohols, with ethyl formate additionally yielding neutral ethanol. Isopropyl- and tert-butyl formate ions readily shed stable radicals and neutral alkenes, alongside methanol loss. Phenyl formate exhibits a unique behavior, involving phenyl radical loss akin to isopropyl- and tert-butyl formate, alongside CO loss similar to methyl- and ethyl formate. The investigation leverages density functional theory to elucidate minimum energy reaction pathways for each ion, with CBS-QB3 single-point energy calculations providing reliable energetics. These insights deepen our understanding of the atmospheric chemistry of formate-derived esters, contributing to the broader understanding of atmospheric processes. Chapter 6 explores the gas-phase dissociation of protonated chloroformates, prevalent in the atmosphere due to their utilization as fuel additives and industrial solvents. Tandem mass spectrometry was employed to scrutinize the unimolecular dissociation of protonated methyl (1), ethyl (2), neopentyl (3), and phenyl chloroformate (4). Notably, 1 and 4 exhibited common HCl loss, yielding CH₃OCO⁺ and C₆H₅OCO⁺, respectively, with 1 additionally generating neutral methanol and ClCO⁺. 4 additionally loses CO and CO₂. In contrast, 2 and 3 each only exhibit a single fragmentation channel, with 2 losing C₂H₄ to generate protonated chloroformic acid and 3 generating protonated 2-methylbutene by losing neutral chloroformic acid. Density functional theory at the B3LYP/6-311+G(d,p) level of theory was employed to explore minimum energy reaction pathways for each ion, and CBS-QB3 single-point energy calculations were used to provide reliable energetics. RRKM (Rice-Ramsperger-Kassel-Marcus) calculations of the rate constants for selected competing processes were carried out to link theory and experiment. One common process observed was the 1,3-H shift of the proton from the carbonyl oxygen to the ester oxygen before dissociation.
Keywords: Formates; RRKM; Chloroformate; Mass spectrometry; ESI; Water Cluster Ions